Analisis Manajemen Mutu Terpadu di PT Madu Pramuka Cibubur Jakarta Timur - A Sukmawati; H.C H Siregar; C Mauidah (Faculty of Animal Science, Bogor Agricultural University, 2007)
The study was conducted to determine the critical component of a Total Quality Management (TQM) Program. The objectives of this research were: (1) identifying the problems of TQM implementation and, (2) analyzing of TQM performace in PT Madu Pramuka. Data were collected from PT Madu Pramuka through an expert survey instrument. Data analysis was done through Analytical Hierarchy Process (AHP). Results of this study indicated that the most important problem was the quality of raw material (honey) which were still under the standard. This is due to limited honey quality control tools. The TQM performance was not satisfying because it was only storage and packaging division used standard as the critical component of TQM. Key words: Total Quality Management, honey, expert survey, Analytical Hierarchy Proces